Effect of clomiphene citrate treatment on the Sertoli cells of dysmetabolic obese men with low testosterone levels. (18th November 2019) - Pelusi, Carla; Fanelli, Flaminia; Baccini, Margherita; Triggiani, Vincenzo; Bartolomeo, Nicola; Carbone, Matteo Domenico; De Pergola, Giovanni; Di Dalmazi, Guido; Pagotto, Uberto; Pasquali, Renato; Giagulli, Vito Angelo
Abstract: Background: Clomiphene citrate (CC) has been shown to restore the hypothalamic‐pituitary‐gonadal (HPG) axis by increasing testosterone (T) levels to physiological levels in patients with dysmetabolic conditions such as obesity, metabolic syndrome and type 2 diabetes mellitus (T2DM). However, the data are unclear regarding the effects on Sertoli cell (SC) function. Aim: To study SC function by assessing Inhibin B (IB) and anti‐Mullerian hormone (AMH) levels at baseline and after 3 months of CC treatment. Materials and methods: This is an ancillary study of a cross‐over, randomised, double‐blind, placebo‐controlled trial performed to evaluate androgen response to CC treatment in dysmetabolic obese subjects with low T levels treated with metformin. We evaluated SC function by assessing IB and AMH levels at baseline and after 3 months of each treatment in ten dysmetabolic obese subjects with low T levels. In all subjects, the influence of the clinical characteristics, metabolic and hormonal baseline parameters on SC and Leydig (LC) function, evaluated respectively with AMH, IB, follicle‐stimulating hormone (FSH) and T levels, was tested. Results: No significant changes were observed for IB and AMH concentrations after each treatment period. Whereas T and oestradiol (E2) levels were shown to be significantly higher in the CC plus metformin phase (CC/Met) only. No clinical, metabolic or hormonal parameters showed significant effects on serum AMH at baseline or after treatments. However, baseline T, dihydrotestosterone (DHT) and E2 positively affected IB levels during CC/Met therapy ( P = .003, P = .038 and P = .049, respectively). Baseline leptin and FSH had a negative ( P = 031) and positive ( P = .048) respectively role on T levels during CC/Met, as they were statistically significant compared to the placebo period (Plac/Met). Conclusion: Unlike the LC activity, CC was unable to influence SC function, as shown by the lack of IB and AMH serum modifications, thus suggesting an intrinsic nonreversible defect of SC cells in patients with dysmetabolic conditions.